Plant Ribosomal Proteins, RPL12 and RPL19, Play a Role in Nonhost Disease Resistance against Bacterial Pathogens - Nagaraj, Satish; Senthil-Kumar, Muthappa; Ramu, Vemanna S.; Wang, Keri; Mysore, Kirankumar S. (Frontiers in Plant Science, 2016)
Characterizing the molecular mechanism involved in nonhost disease resistance is important to understand the adaptations of plant-pathogen interactions. In this study, virus-induced gene silencing (VIGS)-based forward genetics screen was utilized to identify genes involved in nonhost resistance in Nicotiana benthamiana. Genes encoding ribosomal proteins, RPL12 and RPL19, were identified in the screening. These genes when silenced in N. benthamiana caused a delay in nonhost bacteria induced hypersensitive response (HR) with concurrent increase in nonhost bacterial multiplication. Arabidopsis mutants of AtRPL12 and AtRPL19 also compromised in nonhost resistance. The studies on NbRPL12 and NbRPL19 double silenced plants suggested that both RPL12 and RPL19 act in the same pathway to confer nonhost resistance. Our work suggests a role for RPL12 and RPL19 in nonhost disease resistance in N. benthamiana and Arabidopsis. In addition, we show that these genes also play a minor role in basal resistance against virulent pathogens.